2020
DOI: 10.3390/nu12123845
|View full text |Cite
|
Sign up to set email alerts
|

Home Cooking Is Related to Potential Reduction in Cardiovascular Disease Risk among Adolescents: Results from the A-CHILD Study

Abstract: This study aimed to investigate the association between the frequency of home cooking and cardiovascular disease risk among Japanese adolescents. We used cross-sectional data on adolescents from the 2018 Adachi Child Health Impact of Living Difficulty study, which targeted junior high school students aged 13–14 years in Adachi, Tokyo, Japan. Frequency of home cooking by 553 caregivers was assessed via questionnaire and classified as high (almost daily), medium (4–5 days/week), or low (≤3 days/week). Cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…44 It was interesting to note that cooking with clean fuel and kitchen ventilation for a short time (<1.5 h/day) was associated with low prevalent depressive symptoms. Several previous studies indicated that home cooking was associated with a low risk of cardiovascular disease and obesity, 47,48 and a beneficial factor of longevity. 49 These results may be explained by individuals who cooked at home have higher levels of physical activity and diet quality rather than the ones who did not cook by themselves, 48,49 which indirectly indicated our results are reasonability.…”
Section: Discussionmentioning
confidence: 99%
“…44 It was interesting to note that cooking with clean fuel and kitchen ventilation for a short time (<1.5 h/day) was associated with low prevalent depressive symptoms. Several previous studies indicated that home cooking was associated with a low risk of cardiovascular disease and obesity, 47,48 and a beneficial factor of longevity. 49 These results may be explained by individuals who cooked at home have higher levels of physical activity and diet quality rather than the ones who did not cook by themselves, 48,49 which indirectly indicated our results are reasonability.…”
Section: Discussionmentioning
confidence: 99%
“…or not being able to cook [30] . Besides, women pay more attention to health and wellness than men in terms of dietary nutrition and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Tehran Lipid and Glucose Study results showed that more fast food consumption was accompanied by increased in TG levels and TG to HDL-C ratio after three years of follow-up [32] . As the frequency of FAFH increases, there is a corresponding decrease in the frequency of home cooking, and recent studies have shown that teens with low home cooking frequency have lower HDL cholesterol compared with teens with high home cooking frequency (β = -6.15, 95% CI: -11.2, 1.07) [30] . FAFH provides consumers with more food choices, but manufacturers ignore nutrition in pursuit of taste, so FAFH consumers should pay more attention to dietary nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The five response items were: 'almost every day', '4-5 days/week', '2-3 days/week', 'a few days/month', and 'rarely'. We defined <3 times a week as low frequency of home cooking because it was reported to be associated with child obesity and cardiovascular risk [12,13].…”
Section: Frequency Of Home Cookingmentioning
confidence: 99%
“…Beyond dietary outcomes, a population-based study in the United Kingdom showed that more frequent consumption of home-cooked meals was associated with a greater likelihood of having normal weight and body fat status among adults [11]. Studies on Japanese children and adolescents showed that infrequent home cooking was associated with obesity, higher blood pressure, and lower high-density lipoprotein-cholesterol [12,13].…”
Section: Introductionmentioning
confidence: 99%